A Systematic Review of the Risk and Concern of Generative AI Integration in Education - Idris, Irmanyadi; M. Nasir, M. Khalid (Advances in Humanities and Contemporary Studies, 2026)
With the rapid advancement of generative AI, it is concerning that institutions and educators continue to neglect clarifying the risks involved when digital tools are rapidly integrated into education systems without adequate planning and consideration. This systematic literature review seeks to identify and compile these risks, with the aim of providing a comprehensive overview of the challenges faced by students, educators, and institutions when generative AI is adopted within educational contexts. The risks can be categorized into four constructs: ethical integrity, academic integrity, cognitive risk, and technical risk. Each construct requires distinct sets of solutions to effectively mitigate the associated challenges. Consequently, new educational policies must be introduced. Such policies should remain flexible to accommodate cultural variations, differing levels of acceptance, and varying expectations, while simultaneously fostering a fair and inclusive educational environment for all stakeholders involved.